Estimates of uncertainty around budget forecasts - John Clark; Caroline Gibbons; Susan Morrissey; Joshua Pooley; Emily Pye; Rhett Wilcox; Luke Willard (The Australian Government, The Treasury, 2013)
We use past forecast errors to construct confidence intervals around Australian Government Budget forecasts of key economic and fiscal variables. These confidence intervals provide an indication of the extent of uncertainty around the point estimate forecasts presented in the Budget.
Keywords: E17; H68; 330; Confidence intervals; forecast errors